Potential factors that may promote successful cognitive aging - Vance DE (Dove Medical Press, 2012)
David E VanceCenter for Nursing Research, School of Nursing, Edward R Roybal Center for Translational Research in Aging and Mobility, University of Alabama at Birmingham (UAB), Birmingham, AL, USAAbstract: With the unprecedented number of older adults worldwide, it is important to consider ways of facilitating successful cognitive aging. One way to think of this is by augmenting or bolstering cognitive reserve. Loosely defined, cognitive reserve is considered a neurological reservoir that can be depleted by physiological insults (eg, white matter hyperintensities, oxidative stress) to the brain but yet maintain optimal cognitive functioning. Cognitive reserve is built up or depleted by processes of positive and negative neuroplasticity, respectively. Lifestyle factors such as physical exercise (+), mental stimulation (+), good sleep hygiene (+), substance abuse (-), sedentary lifestyle (-), chronic stress and depression (-), social isolation (-), and poor health (-) can either promote or discourage positive and negative neuroplasticity, which in turn impacts cognitive reserve. Nurses are encouraged to understand these processes so they can help facilitate successful cognitive aging in their patients.Keywords: cognitive reserve, Alzheimer's disease, neuroplasticity